2023
DOI: 10.3390/su15043741
|View full text |Cite
|
Sign up to set email alerts
|

Technological Challenges and Opportunities to Plastics Valorization in the Context of a Circular Economy in Europe

Abstract: The transition to a fully-fledged circular economy (CE) has proven to be challenging for many industries. Despite possible competitive advantages of moving industries towards CE activities, their practical implementation is still limited. This communication article delivers ad interim an identification of technological challenges and opportunities for the European plastics industries to facilitate circularity ambitions. In applying the qualitative-empirical Gioia-method utilizing the GABEK-WinRelan tool, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…They studied how certain factors hinder or promote systemic "eco-efficient" CE innovation in the European polyurethane plastic industry and proposed how to facilitate and further develop the management of systemic CE innovation activities. The authors Schultz and Reinhardt (2023) extended their study and, in the next article, described how to facilitate CE's ambitions by overcoming technological challenges and identifying opportunities in the European plastics industry. The authors found that the technological challenges in the plastics sector are mainly related to the contamination of secondary materials, recycling problems, production processing problems, the quality problems of production materials, and quality problems of final products, while opportunities are related to the effective management of secondary materials; chemical recycling innovations; production and processing innovations; and innovative materials and innovative final products.…”
Section: Trade In Recyclable Raw Materialsmentioning
confidence: 99%
“…They studied how certain factors hinder or promote systemic "eco-efficient" CE innovation in the European polyurethane plastic industry and proposed how to facilitate and further develop the management of systemic CE innovation activities. The authors Schultz and Reinhardt (2023) extended their study and, in the next article, described how to facilitate CE's ambitions by overcoming technological challenges and identifying opportunities in the European plastics industry. The authors found that the technological challenges in the plastics sector are mainly related to the contamination of secondary materials, recycling problems, production processing problems, the quality problems of production materials, and quality problems of final products, while opportunities are related to the effective management of secondary materials; chemical recycling innovations; production and processing innovations; and innovative materials and innovative final products.…”
Section: Trade In Recyclable Raw Materialsmentioning
confidence: 99%
“…Against this backdrop, two central ideas have emerged in recent scholarship. First, the transition to a CE must be supported by stakeholder collaborations (Marjamaa et al, 2021; Rincón‐Moreno et al, 2022; Seles et al, 2022; Tapaninaho & Heikkinen, 2022), which may be particularly wide‐ranging if they stretch beyond industrial or even sectoral boundaries (De Angelis et al, 2018; Fischer & Pascucci, 2017; Schultz & Reinhardt, 2022, 2023). Second, it is widely understood that the CE paradigm entails systemic change at the macro, meso, and micro levels (e.g., Kirchherr et al, 2017; Korhonen et al, 2018,b; Prieto‐Sandoval et al, 2018), evidently in view of the fact that sustainability is the ultimate objective of the systemic CE concept (Ghisellini et al, 2016; Kennedy & Linnenluecke, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Ordonomics suggests using credible commitments (Williamson, 1983) to improve situational incentives for mutual betterments. This ordonomic perspective has already proven functional in the application to corporate social responsibility, corporate sustainability, and CE research (e.g., Beckmann et al., 2014; Pies et al., 2009, 2014, 2021; Pies & Schultz, 2023; Schultz et al., 2021, 2023, Schultz, 2021, 2022; Schultz & Pies, 2023; Schultz & Reinhardt, 2022, 2023; Schultz & Rhein, 2024). …”
mentioning
confidence: 99%